Phosphatidylcholine Surface Hydration-Dependent Adsorption to Mucin Enhances Intestinal Mucus Barrier Function - Feng, Guangxin (Langmuir : the ACS journal of surfaces and colloids, 2024)
The crucial role of zwitterionic phosphatidylcholines (PC) within mucus gel is essential for maintaining intestinal homeostasis, while the underlying mechanism remains incompletely understood. Herein, we compared the dynamic interfacial adsorption behavior of saturated dipalmitoylphosphatidylcholine (DPPC) and unsaturated dioleoylphosphatidylcholine (DOPC) to intestinal mucin and their impact on the intestinal mucus barrier function. Results of quartz crystal microbalance with dissipation showed that the highly surface-hydrated DPPC vesicles exhibited significantly faster and more extensive adsorption to purified intestinal mucin than the slightly surface-hydrated DOPC vesicles. Utilizing an intestinal Caco-2/HT29-MTX coculture model, we observed that DPPC vesicles adsorbed much more to the mucus gel compared to DOPC vesicles. Additionally, DPPC vesicle adsorption displayed increased wetting, and converse for DOPC vesicles. Interestingly, both of them exhibited nearly the same protective effects against cell injury induced by peptic-tryptic digests of gliadin (PTG). The partial mechanism involved the binding of PTG to DPPC and DOPC within the mucus gel, thereby restricting PTG contact with the underlying epithelial cells. These findings shed light on the intricate interfacial dynamics of PC adsorption to mucin and their implications for maintaining the integrity of the intestinal mucus barrier